The future of modular architecture - Wallance, David (2021)
"The Future of Modular Architecture presents an unprecedented proposal for mass-customized mid- and high-rise modular housing that can be manufactured and distributed on a global scale. Advocating for the adoption of open-source design based on a new modular standard, the book shows how the construction industry and architectural practice may soon be radically reshaped. By leveraging the existing intermodal freight transport system, global supply chains can be harnessed to realize the long-held promise that housing will be a well-designed and affordable industrial product. We are on the cusp of a transformative change in the way we design and build our cities. Author David Wallance argues that modular architecture is profoundly intertwined with globalization, equitable urbanism, and sustainable development. His book addresses these timely issues through a specific approach grounded in fundamental concepts. Going beyond the individual modular building, Wallance forecasts the emergence of a new type of design, manufacturing, and construction enterprise. Written in an approachable style with illustrated examples, the book is a must read for professionals in architecture and design, city planning, construction, real estate, as well as the general reader with an interest in these topics".